Update on oncolytic viral therapy – targeting angiogenesis - Tysome, James R (Dove Medical Press, 2013)
Oncolytic viruses (OVs) have the ability to selectively replicate in and lyse cancer cells. Angiogenesis is an essential requirement for tumor growth. Like OVs, the therapeutic effect of many angiogenesis inhibitors has been limited, leading to the development of more effective approaches to combine antiangiogenic therapy with OVs. Angiogenesis can be targeted either directly by OV infection of vascular endothelial cells, or by arming OVs with antiangiogenic transgenes, which are subsequently expressed locally in the tumor microenvironment. In this review, we describe the development and targeting of OVs, the role of angiogenesis in cancer, and the progress made in arming viruses with antiangiogenic transgenes. Future developments required to optimize this approach are addressed.